Domestic Geographies of Parental and Infant (Co-) Becomings: Home-Space, Nighttime Breastfeeding, and Parent–Infant Sleep. Issue 4 (4th July 2019) - Tomori, Cecilia; Boyer, Kate
Abstract : This article explores how understandings of parental and infant personhood are negotiated in and through the space of the home. We argue that through spatial practices of creating and using (and not using) nurseries, understandings of parental and infant personhood are both made and unmade. Analysis is based on a rich body of ethnographic research undertaken between 2006 and 2009 with eighteen middle-class breastfeeding families and their communities in the United States, which we analyze through lenses of new materialist and Deleuzian theory. We begin by considering some of the ways in which homes are modified by parents-to-be prior to birth, positing these changes as an effort to call forth both particular kinds of embodied interrelations between parents and babies, as well as infant subjects who possess the specific capacity to sleep independently from a young age. We then argue that lived nighttime practice postbirth often confounds planned bodily, affective, and somatic geographies, driven by agentic infants themselves who express their own strong preferences about staying near their parents' bodies to both sleep and breastfeed. Our research reveals parents negotiating how and where they sleep in collaboration with their new infants, often settling on spatial arrangements that do not reflect either expert advice or their own prebirth plans. This work advances scholarship in and beyond geography by furthering understanding of the intimate spaces of early parenting (including nighttime domestic geographies) about which little is currently known, thus extending scholarship across fields of children's geographies, geographies of parenting, geographies of the home, geographies of the night, and geographies of sleep. Key Words: breastfeeding, geographies of the home, infant sleep, materiality, nighttime, parenting.